The thirty gilt pennies - Kelsey, Alice Geer; Joannes, of Hildesheim, d. 1375. Historia Trium Regum; Laite, Gordon (Nashville: Abingdon Press, 1968)
Adaptation of a legend from the twelfth-century manuscript which traces the origin and route of the thirty coins Judas received for betraying Christ.
Translation and adaptation of a part of John of Hildesheim's Historia trium regum.
engund
Keywords: Magi Legends